PEMANFAATAN MEDIA ALTERNATIF DALAM ISOLASI BAKTERI PADA URINE PENDERITA INFEKSI SALURAN KEMIH DI WILAYAH DAERAH BINAAN KELURAHAN DUFA-DUFA KOTA TERNATE - Erpi Nurdin; Jakaria, Febrianti; Hasanuddin, Riskawati (Universitas Mataram, 2024)
Bacteriological examination, especially bacterial culture, is the gold standard for infectious diseases. The very limited availability of culture media encourages the use of alternative media, especially to see the presence of bacteria in the urine of patients with Urinary Tract Infections (UTIs). The price of semi-synthetic culture media is quite expensive and it is difficult for producers to obtain it in the North Maluku region, especially in Ternate City. The use of this alternative media is expected to provide direct benefits to detect the presence of bacteria through the urine of patients with UTIs and improve the knowledge and skills of ATLM cadres regarding the procedure for using alternative media. The use of tuna as one of the alternative media ingredients has not been optimal for the purposes of microbiology laboratory diagnostics. Carried out in the form of socialization which is implemented in the form of lectures, presentations of materials by the community service team with material on the use of alternative media for examining bacteria that cause UTIs. This activity also involves the activeness of participants by working on assessment worksheets and ending with a post-test activity. In the form of knowledge and application of the Use of alternative culture media based on tuna in examining urinary tract infections in the Dufa-Dufa Village community. The test results showed an increase in the percentage of understanding of community service participants, where at the beginning of the activity there were 54% who did not understand UTI and microbiology laboratory examinations, after receiving education there were no more participants who did not understand. In the choice of understanding enough at the beginning of the test 42% and post test 0%. From the criteria understood at the beginning with only 4%, increased to 48%. In the criteria very understood from 0% increased to 52%. The results of the UTI examination through urine culture with alternative media were that there was UTI in 32 people (64%) and the possibility of UTI in 18 people (36%). Increased understanding of the importance of conducting urine culture examinations related to UTI up to 100%, where 48% understood and 52% understood very much. There were 64% of participants with UTI and the possibility of UTI 36%.